Adaptasi Komunikasi Mahasiswa Digital Freelancer Dalam Lingkungan Kerja Internasional - Muhammad Arief Rahman; Agnita Yolanda (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This study aims to understand the communication adaptation experiences of student digital freelancers when interacting with international clients. The study focuses on adjustments in language, communication styles, work culture, information management, and the selection of digital communication media in cross-border work interactions. A qualitative method with a phenomenological approach was employed, using the perspective of Computer-Mediated Communication (CMC). Data were collected through in-depth interviews and documentation involving three student digital freelancers with experience working with international clients. The data were analyzed through data reduction, data display, and conclusion drawing, and were subsequently interpreted based on the CMC dimensions of accessibility, speed, amount, cognitive effectiveness, relevance, and motivating. The findings show that students adapt their communication by simplifying language and messages, clarifying information, adjusting to clients’ work cultures and communication rhythms, and selecting communication media according to the needs of particular interactions. These adaptations not only help reduce potential miscommunication but also serve as a continuous learning process through which students understand client characteristics, develop mutual understanding, and improve their digital communication competencies. The study demonstrates that communication adaptation is an essential competency for student digital freelancers in establishing and maintaining effective working relationships within international work environments.